Habilidades de alimentação oral de recém-nascidos pré-termo: avaliação e estimulação - Bolzan, Geovana de Paula (2015)
This research aimed to assess the accuracy of the Preterm Oral Feeding Readiness Scale (POFRAS) on the beginning of oral feeding in preterm infants and to verify the accordance of the results of this instrument with those from the oral feeding skill level evaluation. Also, to compare the effectiveness of sensorimotor oral stimulation (SMOS) programs and of a vibratory stimulus combined with SMOS program on feeding transition and length of hospital stay of preterm infants. The study was conducted in three stages. In the first, 82 preterm infants were assessed by POFRAS regarding their readiness to initiate oral feeding and by oral feeding skill level evaluation according to their feeding performance during the first oral feeding. In the second stage, 55 preterm infants with low oral ability were allocated into two groups that received SMOS through Nonnutritive Oral Motor Therapy (NNOMT) and Premature Infant Oral Motor Intervention (PIOMI) programs. Finally, in the third stage, 43 preterm infants were randomly assigned into two groups, who received SMOS through PIOMI, with and without the association of a vibratory stimulus. It was found that POFRAS's accuracy to start oral feeding was average and the results of this instrument showed weak agreement with those obtained in the oral feeding skill level evaluation. There was no difference between the SMOS programs tested on the feeding transition. However, the vibratory stimulus combined with SMOS program seems to contribute to reduce the length of hospital stay of preterm newborns.